Pengaruh Pelatihan Shadow Drill dan Drilling terhadap Kelincahan dan Kecepatan Reaksi Pada Peserta Ekstrakurikuler Bulutangkis - Yustarini, Ni Komang; Semarayasa, I K; Parta Lesmana, K Y; Iwan Swadesi, I K; Hidayat, Syarif (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
This study aims to determine the effect of shadow drill and drilling training on agility and reaction speed. This type of research is quasi experimental with the modified randomized pretest-posttest control group the same subject design. The research subjects used were badminton extracurricular participants of SMK Negeri 3 Singaraja. The data normality test in this study used the Shapiro-Wilk test with the help of SPSS 16.0 at the significance level (α) 0.05. Based on data analysis, the treatment group obtained (1) agility variable 0.791 with significant level 0.083, (2) reaction speed variable 0.939 with significant level 0.276. The calculated significant value is greater than the α value (Sig> 0.05), thus the research hypothesis